Semantic Associations Dominate Over Perceptual Associations in Vowel–Size Iconicity. (July 2019) - Hoshi, Hideyuki; Kwon, Nahyun; Akita, Kimi; Auracher, Jan
We tested the influence of perceptual features on semantic associations between the acoustic characteristics of vowels and the notion of size. To this end, we designed an experiment in which we manipulated size on two dissociable levels: the physical size of the pictures presented during the experiment (perceptual level) and the implied size of the objects depicted in the pictures (semantic level). Participants performed an Implicit Association Test in which the pictures of small objects were larger than those of large objects – that is, the actual size ratio on the semantic level was inverted on the perceptual level. Our results suggest that participants matched visual and acoustic stimuli in accordance with the content of the pictures (i.e., the inferred size of the depicted object), whereas directly perceivable features (i.e., the physical size of the picture) had only a marginal influence on participants' performance. Moreover, as the experiment has been conducted at two different sites (Japan and Germany), the results also suggest that the participants' cultural background or mother tongue had only a negligible influence on the effect. Our results, therefore, support the assumption that associations across sensory modalities can be motivated by the semantic interpretation of presemantic stimuli.